Decolonizing Science: Undoing the Colonial and Racist Hegemony of Western Science - Mirjam Held (Journal of MultiDisciplinary Evaluation, 2023)
Decolonization is the complicated and unsettling undoing of colonization. In a similarly simplified definition, science is a structured way of pursuing knowledge. To decolonize science thus means to undo the past and present racist and colonial hegemony of Western science over other, equally legitimate, ways of knowing. This paper discusses the paradigmatic prerequisites and consequences of decolonizing Western science. Only if Western science is toppled from its pedestal and understood in a cultural way can it engage with other sciences at eye level. Such equal collaboration that results in the co-creation of new knowledge based on the scientific method and Indigenous scientific inquiry is what decolonizing science is all about. What it looks like in practice is highly variable as there is no one-size-fits-all approach due to the fact that Indigenous knowledge is rooted in the local, the land. Therefore, decolonizing science is much more a path than a destination. This path, however, will also pave the way to a new multiparadigmatic space. A quick look into the history and philosophy of science reveals that new paradigms have always emerged after a few trailblazers started engaging in a new way of doing science.